Noncontiguous finished genome sequence and description of Bartonella mastomydis sp. nov. (September 2018) - Dahmani, M.; Diatta, G.; Labas, N.; Diop, A.; Bassene, H.; Raoult, D.; Granjon, L.; Fenollar, F.; Mediannikov, O.
Abstract: Bartonella mastomydis sp. nov. strain 008 is the type strain of B. mastomydis sp. nov., a new species within the genus Bartonella. This strain was isolated from Mastomys erythroleucus rodents trapped in the Sine-Saloum region of Senegal. Here we describe the features of this organism, together with the complete genome sequence and its annotation. The 2 044 960 bp long genomes with 38.44% G + C content contains 1674 protein-coding and 42 RNA genes, including three rRNA genes.